Mothers' Knowledge Before and After Counseling on Child Immunization using Learning Video Media - Herliana, Herliana; Fitria, Rahmah (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
The decline in infant mortality remains a concern, even though it has decreased over the past five decades. Some causes of death can be prevented through immunization. The success of immunization counseling depends on effective and efficient methods.This study aimed to determine the difference in mothers' knowledge levels before and after counseling on child immunization using learning video media. The research used a quasi-experimental design with a one-group pre-test post-test approach. The study population consisted of mothers who attended immunization counseling at the Puskesmas.The results showed that the average mother's knowledge before counseling was 65 (SD = 0.5), categorized as